DISTRIBUTION OF SHRIMP AND CRAB LARVAE IN SEAGRASS BED AT CUA DAI ESTUARY, QUANG NAM PROVINCE (2009-2010) - Ha, Tran Manh; Nhan, Dinh Van (Vietnam Journal of Marine Science and Technology, 2012)
A study on the abundance pattern of shrimp and crab larvae in seagrass beds at Cua Dai estuary was conducted during the field trips of Project KC 09-26/06-10 in April and September 2009. A total of 6 stations in the tidal flat of seagrass beds were selected. Shrimp and crab larvae samples were collected using trawl nets. The result showed that the species composition of demersal larvae is not diverse with 13 species recorded and average abundance is 202 individual/100m2. Penaeidae and Palaemonidae are common families with 5 species/family. Planktonic larvae included 9 taxon with 156 individual/100m3. Penaeidae and Palaemonidae are dominant larvae with 34% and the larvae of Caridae, Crab larvae (megalop stage) with 11% a total of planktonic larvae.